NARASI KETELADANAN NABI DALAM SEJARAH ISLAM SEBAGAI PEDAGOGI MORAL DALAM PENGUATAN REGULASI DIRI SISWA MADRASAH IBTIDAIYAH DI ERA DIGITAL - Fadilatul Janah; Septi Gumiandari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research is motivated by the rise of gadget addiction, impulsive behavior, and the moral crisis in children due to the massive technological transformation. The focus of this research problem is directed at examining the effectiveness of the Prophet's exemplary narrative as a moral pedagogy in strengthening student self-regulation in Islamic elementary schools. Using a descriptive qualitative approach supported by quantitative data, the research's key stages were systematically carried out through participant observation, structured interviews with teachers and parents, a Likert-scale questionnaire, and analysis of lesson plan documentation. Quantitative data were collected from 20 student respondents and analyzed descriptively using percentages. The research findings demonstrate that the integration of interactive storytelling methods, animated videos of the Prophet's story, and contextual reflective discussions significantly stimulate the development of student self-control. Quantitatively, students' understanding of the value of honesty reached 89 percent, responsibility reached 85 percent, and discipline reached 83 percent. Furthermore, achievement in digital self-regulation indicators was high, with 84 percent recognizing the urgency of limiting device use time and 81 percent being more selective in choosing content. The main conclusion confirms that internalizing prophetic stories successfully acts as an effective external moral filter, forming a stronghold of self-regulation resilience in students in the digital era. ABSTRAK Penelitian ini dilatarbelakangi oleh maraknya kecanduan gawai, perilaku impulsif, dan krisis moralitas anak akibat arus transformasi teknologi yang masif. Fokus masalah riset ini diarahkan untuk mengkaji efektivitas narasi keteladanan Nabi sebagai pedagogi moral dalam memperkuat regulasi diri siswa di Madrasah Ibtidaiyah. Menggunakan pendekatan kualitatif deskriptif yang didukung data kuantitatif, tahapan penting penelitian dijalankan secara sistematis melalui observasi partisipatif, wawancara terstruktur bersama guru serta orang tua, pengisian kuesioner skala Likert, dan analisis dokumentasi RPP. Data kuantitatif dihimpun dari 20 responden siswa yang diolah secara deskriptif persentase. Temuan penelitian membuktikan bahwa pengintegrasian metode storytelling interaktif, pemutaran video animasi kisah Nabi, serta diskusi reflektif kontekstual mampu menstimulasi pembentukan kontrol diri siswa secara nyata. Secara kuantitatif, tingkat pemahaman nilai kejujuran siswa menyentuh angka 89 persen, tanggung jawab 85 persen, dan disiplin 83 persen. Selain itu, capaian indikator regulasi diri digital tergolong tinggi, di mana 84 persen siswa menyadari urgensi pembatasan durasi gawai dan 81 persen siswa lebih selektif memilih konten. Simpulan utama menegaskan bahwa internalisasi kisah kenabian sukses bertindak sebagai filter moral eksternal yang efektif membentuk benteng ketahanan regulasi diri siswa di era digital.